THE SPECIFICITY OF PSYCHOLOGICAL CHARACTERISTICS IN GROUPS OF HEALTHY PEOPLE AND PATIENTS WITH EPILEPSY WITH DIFFERENT EFFICIENCY OF ACTIVITY - R. A. Zorin; V. A. Zhadnov; M. M. Lapkin; N. A. Kulikova (Кубанский научный медицинский вестник, 2016)
The results of study of characteristics of motives of activity, anxiety, depression, aggression and neurodynamical personality parameters in group of 72 healthy people and 148 patients with epilepsy with different effectiveness of modeling purposeful activity (test Gorbov-Shulte) are presented. The differences of these parameters in group of patients with different effectiveness of activity and quality of life was estimated. The higher level of anxiety, aggression and low level of social adaptation in group of patients with epilepsy determine approach of mobilizing pshychophysiological resources in realization of alternative biological models of activity which associated with higher frequency of seizures.